2020
DOI: 10.1113/jp279554
|View full text |Cite
|
Sign up to set email alerts
|

Training with blood flow restriction increases femoral artery diameter and thigh oxygen delivery during knee‐extensor exercise in recreationally trained men

Abstract: Key points Endurance‐type training with blood flow restriction (BFR) increases maximum oxygen uptake (V̇O2max) and exercise endurance of humans. However, the physiological mechanisms behind this phenomenon remain uncertain. In the present study, we show that BFR‐interval training reduces the peripheral resistance to oxygen transport during dynamic, submaximal exercise in recreationally‐trained men, mainly by increasing convective oxygen delivery to contracting muscles. Accordingly, BFR‐training increased oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
88
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(103 citation statements)
references
References 40 publications
10
88
1
4
Order By: Relevance
“…Post training, a higher O 2 convective reserve greatly reduced the total net lactate release in the BFR-leg compared to the CON-leg at submaximal intensity. Enhanced O 2 transport and consequently delayed onset of lactate accumulation improved post-training PO in the BFR-leg (11%) (Christiansen et al 2020). This result demonstrates an important impact of BFR on improvement of endurance performance, similar to those reported in previous studies (Sundberg, 1994;Bennett & Slattery, 2019).…”
Section: O 2 Transport and Utilization Adaptations To Bfr Cyclingsupporting
confidence: 88%
See 4 more Smart Citations
“…Post training, a higher O 2 convective reserve greatly reduced the total net lactate release in the BFR-leg compared to the CON-leg at submaximal intensity. Enhanced O 2 transport and consequently delayed onset of lactate accumulation improved post-training PO in the BFR-leg (11%) (Christiansen et al 2020). This result demonstrates an important impact of BFR on improvement of endurance performance, similar to those reported in previous studies (Sundberg, 1994;Bennett & Slattery, 2019).…”
Section: O 2 Transport and Utilization Adaptations To Bfr Cyclingsupporting
confidence: 88%
“…Early studies have demonstrated that aerobic training with a blunted O 2 supply improved aerobic performance and invoked mitochondrial and vascular adaptations (Sundberg, 1994), thus allowing efficient convective and diffusional transport of O 2 to the exercising muscles (Wagner, 1996). In the present study, BFR-training led to a greater increase in thigh O 2 transport and a difference between O 2 delivery and uptake in BFR-leg compared to CON-leg at both exercise intensities (Christiansen et al 2020). By contrast, when performing high intensity knee extensor exercise, O 2 uptake remained unchanged, whereas O 2 delivery increased.…”
Section: O 2 Transport and Utilization Adaptations To Bfr Cyclingsupporting
confidence: 56%
See 3 more Smart Citations